How Large Was the the Output Collapse in Russia? : Alternative Estimates and Welfare Implications - Gavrilenkov, Evgeny (IMF Working Papers; Working Paper ;, 1994)
The divergence between production and consumption indicators in Russia suggests that the magnitude of the output collapse in the course of the transition is overstated by the official statistics. Alternative estimates for real GDP are derived, which reconcile the official production and consumption data. Based on cautious assumptions, real GDP appears to have declined cumulatively by no more than one third rather than by one half. The drop in household welfare is much smaller still, as the output mix shifts and deadweight losses are sharply reduced.